Pengembangan Media Pop-Up Book untuk Meningkatkan Kemampuan Pemecahan Masalah - Hermini; Hardianto, Hardianto; Indah, Indah (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
Abstract. The problems in this study are: 1) what is the procedure for developing pop-up book media, 2) what is the validity of the product being developed, 3) what is the practicality of the product being developed, 4) what are the differences in student learning outcomes before and after using pop-up book media . This study aims to determine: 1) the procedure for developing pop-up book media, 2) the validity of the product being developed, 3) the practicality of the product being developed, 4) knowing the differences before and after student learning outcomes using pop-up book media. The type of research used is Research and Development. The results of this study indicate that the percentage of validity has a high level of validity with the assessment of material experts 95% (very valid), design experts 95% (very valid), linguists 85% (very valid), learning experts 100% (very valid). The results of the practicality analysis have an average value of 91.1%, including the very practical category. The results of the data analysis stated that the pre-test and post-test showed that the average N-Gain Score was 0.69 in the presentation. The N-Gain Score was 69.55%, which was quite effective. The minimum N-Gain value is 20% and the highest is 100%. There is a significant difference in learning outcomes around the flat shape before and after using the pop-up book media, so it can be concluded that the pop-up book media developed is feasible to try out.